2022
DOI: 10.1038/s41598-022-07552-2
|View full text |Cite
|
Sign up to set email alerts
|

Cichlids and stingrays can add and subtract ‘one’ in the number space from one to five

Abstract: The numerical understanding of cichlids and stingrays was examined regarding addition and subtraction abilities within the number space of one to five. Experiments were conducted as two-alternative forced-choice experiments, using a delayed matching to sample technique. On each trial, fish had to perform either an addition or subtraction, based on the presentation of two-dimensional objects in two distinct colors, with the color signaling a particular arithmetic process. Six cichlids and four stingrays success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Remarkably complex behaviors (tool use in the case of C. anchorago and T. hardwicke (Bernardi, 2012; Paśko, 2010), and social cognition in the case of L. dimidiatus (Kohda et al, 2022; McAuliffe et al, 2021; Wismer et al, 2016)) have been reported in the group of wrasses. Cichlids are phylogenetically close to wrasses and display relatively complex social and cognitive behaviors, although no instances of tool use have been observed (Barks and Godin, 2013; Hotta et al, 2019; Schluessel et al, 2022; Snekser and Itzkowitz, 2020). By contrast, no such behaviors have been reported in the “outgroup” species.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably complex behaviors (tool use in the case of C. anchorago and T. hardwicke (Bernardi, 2012; Paśko, 2010), and social cognition in the case of L. dimidiatus (Kohda et al, 2022; McAuliffe et al, 2021; Wismer et al, 2016)) have been reported in the group of wrasses. Cichlids are phylogenetically close to wrasses and display relatively complex social and cognitive behaviors, although no instances of tool use have been observed (Barks and Godin, 2013; Hotta et al, 2019; Schluessel et al, 2022; Snekser and Itzkowitz, 2020). By contrast, no such behaviors have been reported in the “outgroup” species.…”
Section: Resultsmentioning
confidence: 99%
“…Also, due to the fact that tasks become fully automated, it reduces the chance of human errors. Moreover, in combination with the automation, its low cost (Figure 1a, Table 1) We stress that the experimental configuration presented here (a Y-maze setup for two alternative forced choice reversal learning and colour discrimination tasks) is a proof-of-concept but that GoFish's basics could be used without configural changes in multiple other experimental paradigms e.g., quantity discrimination experiments (Potrich et al, 2022;Schluessel et al, 2022), behavioural timing (Talton et al, 1999, foraging (Aw et al, 2009;Newport et al, 2021), object recognition (Newport et al, 2016), and navigation (Burt de Perera & Holbrook, 2012;Newport et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We stress that the experimental configuration presented here (a Y-maze setup for two alternative forced choice reversal learning and colour discrimination tasks) is a proof-of-concept but that GoFish ’s basics could be used without configural changes in multiple other experimental paradigms e.g., quantity discrimination experiments (Potrich et al, 2022; Schluessel et al, 2022), behavioural timing (Talton et al, 1999), foraging (Aw et al, 2009; Newport et al, 2021), object recognition (Newport et al, 2016), and navigation (Burt de Perera & Holbrook, 2012; Newport et al, 2016). GoFish could also be used to implement experiments using a range of set-ups differing to that reported here (e.g., open field and maze configurations that could employ a greater number of screens and/or feeders than we have).…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit, up to which two amounts of presented objects differing by only one item could still be successfully differentiated, was four (Kreuter et al 2021 ), which is similar to most vertebrates (Agrillo 2015 ). A follow up study (Schluessel et al 2022 ) tested the stingray’s addition and subtraction abilities within the number space of one to five. Based on a protocol established for honeybees (Howard et al 2019 ), stingrays learned to perform either an addition or subtraction, depending on the presentation of two-dimensional objects in two distinct colours, with the colour signalling a particular arithmetic process.…”
Section: Numerositymentioning
confidence: 99%